Step-tracking movements of the wrist in humans. I. Kinematic analysis - Hoffman, DS (J Neurosci, 1986)
We have examined the kinematics of the initial trajectory of step- tracking movements performed by human subjects. Each subject tracked a target that required 5–30 degrees of radial or ulnar deviation of the wrist. All movements were to be performed as accurately as possible. Speed instructions were given before each trial. When subjects performed different amplitude movements following the same speed instruction, the peaks of velocity, acceleration, and jerk were linearly related to peak displacement. The peaks of velocity, acceleration, and jerk also changed when the speed instruction was altered. Thus, for any given movement, the peak values of the derivatives of displacement were dependent on both movement amplitude and intended speed. As a result, the peak values of the derivatives cannot be used by themselves to control or monitor peak displacement. When subjects performed different amplitude movements following the same speed instruction, movement duration tended to remain constant. In contrast, movement duration changed when the speed instruction was altered. Movements performed when subjects intended to move slowly had longer durations than when subjects intended to move quickly. These results suggest that subjects volitionally alter intended speed by selecting different movement durations. When both movement amplitude and intended speed were varied, the peak displacement of a step- tracking movement was linearly related to the product of 2 kinematic variables: the initial peak of a derivative of displacement (either velocity, acceleration, or jerk) and movement duration. On the basis of our observations, we propose that central commands generate step- tracking movements of different amplitudes and intended speeds by adjusting both the magnitude and duration of a derivative of displacement.